Structural Load Optimization of 15 MW Offshore Wind Turbine Using LHS-Based Design Space - Sajid Ali; Muhammad Waleed; Daeyong Lee (Journal of Marine Science and Engineering)
The structural integrity of next-generation offshore wind turbines is highly sensitive to inflow variability, yet current standards often simplify wind conditions without capturing their combined effects on dynamic loads. To address this, we analyzed the NREL IEA 15 MW offshore wind turbine using 27 simulation cases strategically selected through Latin Hypercube Sampling (LHS) from a design space of over 14 million combinations. Four key environmental variables—Extreme Wind Speed (30–40 m/s), turbulence intensity (12–16%), Shear Exponent (0.1–0.3), and Flow Inclination Angle (−8° to +8°)—were varied to assess their influence on structural response using BLADED simulations. Results showed that the combined structural moment (Mxyz) ranged from 159,502.5 kNm (minimum) to 189,829.2 kNm (maximum), indicating a 19% increase due to inflow conditions. Maximum-moment case exhibited a 2.6× higher drag coefficient, a 13% rise in pitch bearing moment, and dominant frequency content near 0.175 Hz, closely matching the first tower side-side natural mode (0.17593 Hz), confirming potential resonance. These findings highlight the importance of multidimensional inflow modeling for identifying worst-case load scenarios and establishing a foundation for future load prediction models and support structure optimization.